Struktur Komunitas Gastropoda Pada Persawahan Pasang Surut Dan Tadah Hujan di Kecamatan Sungai Kakap - Mukarlina, Fajar Nico Rudianto, Tri Rima Setyawati, (Jurnal Protobiont, 2014)
Rice farming ecosystems is indispensably important to organism life circle. Gastropoda, taxonomy class within the phylum Mollusca, are mostly found in rice farming. Rice farming environment in sub-district of Sungai Kakap which is defined by irrigation schemes may influence Gastropoda. This study was conducted from March to April 2011. It aims to investigate both the community structure and the habitat of Gastropoda in the rice fields in sub-district of Sungai Kakap. Sample were taken by using Cluster Random Sampling. We found 9 species of Gastropoda namely Pomacea canaliculata, Pila scutata, Brotia spedicea, Lymnaea rubiginosa, Belamnya javanica, Gyraulus convexiusculus, Cerithidae quadrata and Neritina pulligera. Pomacea canaliculata was Gastropoda with the highes density in rice field (0.151 ind/m2) and irrigation canals (11.87 ind/m2). The highest diversity index of Gastropoda in irrigation canals intertidal zone Sungai Itik (H:1.42). Dominance index was highest in irrigation canals rainfed Sungai Itik (1.00) and irrigation canals rainfed Sungai Rengas (1.00). The highest evennes index found in irrigation canals intertidal zone Sungai Rengas (0.99).